Structural Characteristics of Simple RNA Repeats Associated with Disease and their Deleterious Protein Interactions - Ciesiolka, Adam; Jazurek, Magdalena; Drazkowska, Karolina; Krzyzosiak, Wlodzimierz J. (Frontiers in Cellular Neuroscience, 2017)
Short Tandem Repeats are frequent entities in many transcripts, however, in some cases, pathological events occur when a critical repeat length is reached. This phenomenon is observed in various neurological disorders, such as myotonic dystrophy type 1, fragile X-associated tremor/ataxia syndrome, C9orf72-related amyotrophic lateral sclerosis and frontotemporal dementia, and polyglutamine diseases, such as Huntington’s disease and spinocerebellar ataxias. The pathological effects of these repeats are triggered by mutant RNA transcripts and/or encoded mutant proteins, which depend on the localization of the expanded repeats in non-coding or coding regions. A growing body of recent evidence revealed that the RNA structures formed by these mutant RNA repeat tracts exhibit toxic effects on cells. Therefore, in this review, we present existing knowledge on the structural aspects of different RNA repeat tracts as revealed mainly using well-established biochemical and biophysical methods. Furthermore, in several cases, it was shown that these expanded RNA structures are potent traps for a variety of RNA-binding proteins and that the sequestration of these proteins from their normal intracellular environment causes alternative splicing aberration, inhibition of nuclear transport and export, or alteration of a microRNA biogenesis pathway. Therefore, in this review, we also present the most studied examples of abnormal interactions that occur between mutant RNAs and their associated proteins.